Marine Microalgae Tetraselmis suecica as Flocculant Agent of Bio-flocculation Method - Mujizat Kawaroe; Tri Prartono; Adriani Sunuddin; Deni Saputra (HAYATI Journal of Biosciences, 2016)
Microalgae harvesting is an important part in microalgae cultivation system. Techniques for harvesting marine microalgae which are commonly used are centrifugation, filtration and flocculation. These techniques still have some disadvantages, such as not environment friendly, and high usage of energy and cost. Bio-flocculation harvesting technique using microalgae as a flocculant agent can be an alternative way to solve these problems. In this research, mixing of Tetraselmis suecica (flocculant) with Chlorellasp. and Nannochloropsis sp. (non-flocculant) in ratios of 1:4, 2:4, 3:4 and 4:4 (v/v) has been conducted to obtain percent recovery of marine microalgae harvest. The results showed that T. suecica as flocculant agent can fasten the harvesting of Chlorella sp. and Nannochloropsis sp. It was shown by the increase of percent recovery value of Chlorellasp. from 51.14 ± 1.07% to 67.34 ± 0.67% and Nannochloropsis sp. from 20.52 ± 1.17% to 42.43 ± 0.40% during the first hour of flocculating process. Our result showed that bio-flocculation is an environment friendly technique which can be applied to harvest marine microalgae.